To explore the prognostic efficacy and mechanism of ABCC5 clinical scoring model in hepatocellular carcinoma - Deng, Yu; Yang, Ning; Huang, Chengyu; Long, Meiting; Wu, Junming; Mo, Ke; Li, Zijun (Frontiers in Oncology, 2025)
ObjectiveThe study found that ATP-binding cassette subfamily C member 5 (ABCC5) is highly expressed in hepatocellular carcinoma (HCC). It aims to explore ABCC5 role and prognostic value in HCC and uses the DrugBank database to identify potential therapeutic drugs targeting ABCC5, assessing its potential as a biomarker and treatment target for HCC.MethodsRNA-seq and clinical data from TCGA-LIHC and GSE76427 were analyzed to identify ABCC5-associated differentially expressed genes and miRNAs. Weighted gene co-expression network analysis (WGCNA) revealed co-expression modules, and survival analysis assessed prognostic significance. Experimental validation included qRT-PCR, Western blot, migration assays, and drug response studies using the ABCC5 inhibitor zidovudine (ZDV).ResultABCC5 was significantly overexpressed in HCC (p < 0.001) and correlated with poor overall (p = 0.008) and recurrence-free survival (p < 0.0001). WGCNA identified the MEturquoise module (enriched in cell cycle and p53 pathways) strongly linked to ABCC5 (r = 0.54). Immune infiltration analysis showed ABCC5 high-expression associated with Treg accumulation (immune suppression) and reduced mast cells. ZDV suppressed ABCC5 expression (~50%), activated p53 signaling (p53↑2.0-fold), and inhibited HCC migration and proliferation more effectively than the ABCC5-specific inhibitor MK-571. Somatic mutations (5% missense) and methylation (cg14480679, r = -0.43) further implicated ABCC5 in HCC progression. The ABCC5-based prognostic model, validated by calibration curves, independently predicted survival (p < 0.0001).ConclusionThis study constructed an ABCC5 clinical model and discovered that ABCC5 can serve as both a prognostic biomarker and therapeutic target for HCC. Multi-omics analysis and experimental validation confirmed that ABCC5 drives HCC progression by participating in immune microenvironment reprogramming, affecting cell cycle progression, and regulating the p53 signaling pathway. The research not only identified potential diagnostic markers and therapeutic targets, but the established prognostic model also provides new insights for investigating HCC pathogenesis and clinical translation.